2019
DOI: 10.1128/jvi.00827-19
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of PD-1 and LAG-3 Immune Checkpoints Combined with Vaccination Restores the Function of Antiviral Tissue-Resident CD8+TRMCells and Reduces Ocular Herpes Simplex Infection and Disease in HLA Transgenic Rabbits

Abstract: Chronic viruses such as herpes simplex virus 1 (HSV-1) evade the hosts’ immune system by inducing the exhaustion of antiviral T cells. In the present study, we found that exhausted HSV-specific CD8+ T cells, with elevated expression of programmed death ligand-1 (PD-1) and lymphocyte activation gene-3 (LAG-3) receptors were frequent in symptomatic patients, with a history of numerous episodes of recurrent corneal herpetic disease, compared to asymptomatic patients who never had corneal herpetic disease. Subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 68 publications
(147 reference statements)
2
27
0
Order By: Relevance
“…Exhaustion of HSV-specific CD8 + T cells may occur during multiple productive replication attempts and/or repetitive virus reactivations, events that might be underestimated with actual molecular detections 73 . Moreover, we found that LAG-3 and PD-1 immune checkpoints blockade in HSV-1 latently infected HLA Tg rabbits restored T cell functions associated with less recurrent ocular herpes infection and disease, confirming our previous studies 18,28,31,35 . The findings in this report prompt to question whether HSV-1 infections can be categorized as a latent or chronic infection.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Exhaustion of HSV-specific CD8 + T cells may occur during multiple productive replication attempts and/or repetitive virus reactivations, events that might be underestimated with actual molecular detections 73 . Moreover, we found that LAG-3 and PD-1 immune checkpoints blockade in HSV-1 latently infected HLA Tg rabbits restored T cell functions associated with less recurrent ocular herpes infection and disease, confirming our previous studies 18,28,31,35 . The findings in this report prompt to question whether HSV-1 infections can be categorized as a latent or chronic infection.…”
Section: Discussionsupporting
confidence: 91%
“…flow cytometry assays. Trigeminal ganglia were analyzed by flow cytometry, as we previously reported 86 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Related studies show that both CD4 + T-cells and CD8 + T-cells in draining lymph nodes have increased expression levels of PD-1, TIM-3, and LAG-3 after HSV infection [86,87]. This upregulated PD-1 and LAG3 expression led to the exhaustion of tissue-resident CD8 + T-cells and the loss of antiviral response to symptomatic reactivation, whereas a blockade of LAG-3 and PD-1 improved the function of HSV-specific CD8 + T-cells and significantly reduced the reactivation of latent HSV virus in a rabbit model [88,89].…”
Section: Immune Checkpoints In Other Virusesmentioning
confidence: 97%
“…There is substantial literature currently on the role of CD8 ϩ T cells in the protection against herpes, whereas the role of CD4 ϩ T cells in such protection is relatively less known (10)(11)(12)(13)(14). Activated CD4 ϩ T cells are retained in latently infected trigeminal ganglia (TG) of mice and humans.…”
mentioning
confidence: 99%